The Correlation of Training Intensity and Taekwondo Athlete's Physical Fitness Level - Anggraeni, Dewi; Syafei, Muhamad; Suhartoyo, Topo; Surijati, Katri Andini; Widanita, Neva (Physical Activity Journal (PAJU), 2024)
The research investigates the physiological responses correlated with varying training intensities. This research determines the correlation between routine taekwondo training intensity and physical fitness in achievement class athletes at the Satria Taekwondo Academy Club, Purwokerto. The quantitative correlational research method uses a single-group experimental pre-test and post-test design method without posing any particular threat to the research sample. This research involved athletes' achievement development classes at the Satria Academy Taekwondo Club Purwokerto as samples. The research involves 30 respondents. Physical fitness was examined using the Multistage Fitness Test (running to the rhythm). The results reveal that while the majority of respondents are in the "Average" category, there is a concerning prevalence of individuals classified as "Poor" and "Bad." The examination of aerobic fitness levels among the 30 Taekwondo athletes reveals significant insights into the correlation between specialized training and cardiovascular performance